Pengaruh Pengalaman Mengajar, Supervisi Akademik, dan Motivasi Berprestasi terhadap Kinerja Guru Penjas SMK di Bantul - Winarto, Ari (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to determine the contribution of teaching experience, academic supervision of school principals and achievement motivation to the performance of State Vocational School physical education teachers in Bantul Regency for the 2022/2023 academic year,the research aims to analyze the influence of: The contribution of teaching experience to teacher performance. The contribution of the principal's academic supervision to teacher performance. Contribution of achievement motivation to the performance of State Vocational School physical education teachers in Bantul Regency. This research uses a quantitative type of research. The population in this study were all State Vocational School physical education teachers in Bantul Regency, consisting of 29 teachers. The data collection technique uses a questionnaire in the form of a questionnaire. The data analysis technique uses multiple regression analysis. After carrying out validity and reliability tests, it was found that of all the questions consisting of 30 questions on teacher performance variables, 30 questions on teaching experience variables, 30 questions on principal academic supervision variables and 30 questions on achievement motivation variables, all were declared valid and reliable. The results of this research show that: There is a joint positive and very significant influence between teaching experience, the principal's academic supervision and achievement motivation on teacher performance. This means that the higher the teaching experience, the principal's academic supervision and the teacher's achievement motivation, the better the teacher's performance will be. Vice versa, if the teaching experience, academic supervision of the principal and achievement motivation in the place where the teacher works is low/poor, then the performance produced by the teacher will also be low/bad. There is a positive and significant influence between teaching experience on teacher performance, there is a positive but not significant influence between the principal's academic supervision on teacher performance, there is a positive and insignificant influence of work achievement motivation on teacher performance. Of the three independent variables, the one that has the dominant influence on the performance of State Vocational School physical education teachers in Bantul Regency is teacher work motivation.